China's evolving reserve requirements - Guonan Ma; Yan Xiandong; Liu Xi (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
This paper examines the evolving role of reserve requirements as a policy tool in China. Since 2007, the Chinese central bank (PBC) has relied more on this tool to withdraw domestic liquidity surpluses, as a cheaper substitute for open-market operation instruments in this period of rapid FX accumulation. China's reserve requirement system has also become more complex and been used to address a range of other policy objectives, not least being macroeconomic management, financial stability and credit policy. The preference for using reserve requirements reflects the size of China's FX sterilisation task and the associated cost considerations, a quantity-oriented monetary policy framework challenged to reconcile policy dilemmas and tactical considerations. The PBC often finds it easier to reach consensus over reserve requirement decisions than interest rate decisions and enjoys greater discretion in applying this tool. The monetary effects of reserve requirements need to be explored in conjunction with other policy actions and not in isolation. Depending on the policy mix, higher reserve requirements tend to signal a tightening bias, to squeeze excess reserves of banks, to push market interest rates higher, and to help widen net interest spreads, thus tightening domestic monetary conditions. There are, however, costs to using this policy tool, as it imposes a tax burden on Chinese banks that in turn appear to have passed a significant portion of this cost onto their customers, mostly depositors and SMEs. However, the pass-through onto bank customers appears to be partial.
URN:NBN:fi:bof-201408071936
Keywords: E40; E50; E52; E58; E60; H22; 330; reserve requirements; sterilisation tools; monetary policy; net interest margin and spread; tax incidence; Chinese economy